Effectiveness of acupuncture as adjunctive therapy in type 2 diabetic: study protocol for a randomized controlled trial - Cheok, Yean Chin; Mohd Shariff, Zalilah; Mun, Chan Yoke; Yein, Lee Ping; Chuan, Ng Ooi (Research Square Platform, 2022)
Background: The incidence of type 2 diabetes mellitus is increasing worldwide. The literature suggests that acupuncture is a possible complementary therapy for type 2 diabetes mellitus. This study aims to determine the effect of acupuncture as an adjunctive therapy on homeostasis model assessment-insulin resistance (HOMA-IR), adiposity and health-related quality of life (HRQOL) in patients with type 2 diabetes mellitus. Method and design: This randomised, double-blind, placebo controlled and parallel design trial will be carried out in three public university teaching hospitals in Malaysia. Eligible type 2 diabetes mellitus subjects will be randomly assigned to receive either acupuncture (n=30) or a placebo (n=30). The intervention is carried out using acupuncture ‘press’ needle on abdomen area (10 sessions of treatment), twice a week over 6 weeks. Both groups will continue with their routine diabetes care. Primary outcome of HOMA-IR and secondary outcomes of body mass index and waist circumference will be measured at the time of recruitment (baseline) and after completion of 10 sessions (week 7) of the treatment. Additionally, secondary outcome of HRQOL will be measured at the time of recruitment (baseline), after completion of 5 sessions (week 3/4) and 10 sessions (week 7) of the treatment. Any adverse event will be recorded at every visit. Discussion: The ndings of this study will provide important clinical evidence for the effect of acupuncture as adjunctive therapy on HOMA-IR, adiposity and HRQOL of type 2 diabetes mellitus.